Characterization of Radiation Exposure at Aviation Flight Altitudes Using the Nowcast of Aerospace Ionizing Radiation System (NAIRAS) - Daniel B. Phoenix; Chris J. Mertens; Guillaume P. Gronoff; Kent Tobiska (Space Weather)
Abstract Exposure to ionizing radiation from galactic cosmic rays (GCR) and solar energetic particles (SEP) at aircraft flight altitudes can have an adverse effect on human health. Although airline crews are classified as radiation workers by the International Commission on Radiological Protection (ICRP), in most countries, their level of exposure is unquantified and undocumented throughout the duration of their career. As such, there is a need to assess pilot ionizing radiation exposure. The Nowcast of Aerospace Ionizing RAdiation System (NAIRAS), a real‐time, global, physics‐based model is used to assess such exposure. The Automated Radiation Measurements for Aerospace Safety (ARMAS) measurement data set consists of high latitude, high altitude, and long‐duration aircraft flights between 2013 and 2023. Here, we characterize radiation exposure at aviation flight altitudes using the NAIRAS model and compare with 45 flight trajectories from the recent ARMAS flight measurement inventory.